Report by Poznań biology students on an educational expedition to Kherson Region, Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The article comprises a report from an educational expedition students of Faculty of Biology at Adam Mickiewicz University to the Kherson Oblast, which was possible thanks to the cooperation with Kherson State University. The aim was to get acquainted with the natural peculiarities of the central part of southern Ukraine, inter alia two national reserve Askania Nova Reserve and Black Sea Biosphere Reserve.
Keywords: educational expedition, Kherson Oblast, southern Ukraine.